2018
DOI: 10.1596/1813-9450-8670
|View full text |Cite
|
Sign up to set email alerts
|

Promoting Early Childhood Development through Combining Cash Transfers and Parenting Programs

Abstract: The Policy Research Working Paper Series disseminates the findings of work in progress to encourage the exchange of ideas about development issues. An objective of the series is to get the findings out quickly, even if the presentations are less than fully polished. The papers carry the names of the authors and should be cited accordingly. The findings, interpretations, and conclusions expressed in this paper are entirely those of the authors. They do not necessarily represent the views of the International Ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 47 publications
2
22
0
Order By: Relevance
“…Experimental evidence from similar interventions, now available for at least 11 low and middle income countries, generally confirms positive impacts on early childhood development, though effect sizes vary substantially, and delivering effective interventions at scale has proved challenging (Jeong et al, 2018;Attanasio et al, 2020;J-PAL, 2020;Arriagada et al, 2018). In a similar context as the current study, Macours et al (2015) find positive but small effects of a home visit parenting program.…”
Section: Introductionsupporting
confidence: 70%
“…Experimental evidence from similar interventions, now available for at least 11 low and middle income countries, generally confirms positive impacts on early childhood development, though effect sizes vary substantially, and delivering effective interventions at scale has proved challenging (Jeong et al, 2018;Attanasio et al, 2020;J-PAL, 2020;Arriagada et al, 2018). In a similar context as the current study, Macours et al (2015) find positive but small effects of a home visit parenting program.…”
Section: Introductionsupporting
confidence: 70%
“…This short paper is based on the World Bank Policy Research Paper No. 8670 by Arriagada et al (2018).…”
Section: Acknowledgementsmentioning
confidence: 96%
“…While there is a solid theory of change supported by the evidence, operationalizing the integration of the CT with the parenting intervention requires an assessment of the context and the availability of other service providers. After reviewing 10 case studies, we identified four models to guide the decision: integrated, convergence, alignment and piggybacking (Arriagada et al, 2018).…”
Section: Models For Combining Cts and Parenting Programsmentioning
confidence: 99%
See 1 more Smart Citation
“…Evaluations find that parenting interventions can improve child development outcomes, notably in cognition and language development. Existing evidence (as summarized in Arriagada et al, 2018) from successful parenting programs identify multiple key features for success, including: (i) target both parents (not just mothers), (ii) include demonstrations with children and opportunities to practice and receive feedback during the training sessions, (iii) invest in strong program protocols and materials to ensure consistency, (iv) establish a frequent and supportive supervision scheme including on-the-job training and coaching for field staff, and (v) invest in a monitoring and evaluation system for quality assurance.…”
Section: How Can Pantawid Strengthen Its Impact On Nutrition?mentioning
confidence: 99%